Assessing the Genotoxicity of Cellulose Nanomaterials in a Co-Culture of Human Lung Epithelial Cells and Monocyte-Derived Macrophages - Ventura, Célia (2023)
Funding Information: The work was funded by the Portuguese Foundation for Science and Technology (FCT/MCTES), through national funds (PIDDAC) under the project ToxApp4NanoCELFI (PTDC/SAU-PUB/32587/2017). The authors also acknowledge the support of FCT/MCTES to the following projects: LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication-i3N, CIEPQPF (UIDB/00102/2020) and ToxOmics, NMS-UNL (UIDP/00009/2020; UIDB/00009/2020). Thanks also to European Cooperation in Science & Technology (COST) Action: CA21159—Understanding interaction light—biological surfaces: possibility for new electronic materials and devices (PhoBioS); Inpactus Project—innovative products and technologies from eucalyptus (Project No. 21874 funded by Portugal 2020 through ERDF in the frame of COMPETE 2020 No. 246/AXIS II/2017). Publisher Copyright: © 2023 by the authors.